1997
DOI: 10.1103/physrevlett.79.2875
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Fundamental Length Scales in the Vortex State ofYBa2Cu3O6.60

Abstract: The internal field distribution in the vortex state of YBa 2 Cu 3 O 6.60 is shown to be a sensitive measure of both the magnetic penetration depth l ab and the vortex-core radius r 0 . The temperature dependence of r 0 is found to be weaker than in the conventional superconductor NbSe 2 and much weaker than theoretical predictions for an isolated vortex. The effective vortex-core radius decreases sharply with increasing H, whereas l ab ͑H͒ is found to be much stronger than in NbSe 2 . [S0031-9007 (97)04251-8] … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 25 publications
5
49
0
Order By: Relevance
“…On the other hand, we expect that rather weak shrinkings of vortex core observed in NbSe 2 (Refs. 26,28,29,30) and CeRu 2 (Ref. 32) may be explained partly in terms of the impurity effect, i.e., the vortex core shrinkage approximately linear in T with moderate curvature and its saturation towards a finite value in zero-temperature limit ( Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, we expect that rather weak shrinkings of vortex core observed in NbSe 2 (Refs. 26,28,29,30) and CeRu 2 (Ref. 32) may be explained partly in terms of the impurity effect, i.e., the vortex core shrinkage approximately linear in T with moderate curvature and its saturation towards a finite value in zero-temperature limit ( Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, µSR experiments were performed on the s-wave superconductor NbSe 2 to observe the KP effect. 26,28,29,30 The experimental data of spin precessions, which correspond to the Fourier transformation of the Redfield pattern (the magnetic field distribution) of a vortex lattice, are fitted by a theoretical formula, 31 extracting the information on the spatial profile of the supercurrent density j(r) around vortices. 26,28 While a shrinking vortex core was observed, it was weaker than the theoretical expectation of the KP effect for a clean superconductor.…”
Section: Introductionmentioning
confidence: 99%
“…It may well, since the coherence length [21,22] is ξ ≈ 80 − 200Å for x = 0.60 − 0.57, much larger than the characteristic length scale of the SC stripes mentioned above. Although the presence of SC below T f might be retrieved from µSR lineshape analysis, as it was attempted by modeling the complex internal field distribution in a single crystal [9], this is beyond the scope of our polycrystalline data and we reverted directly to SQUID magnetization measurements.…”
Section: −1mentioning
confidence: 93%
“…However, it can be inferred indirectly [98][99][100][101][102] in various ways, and for the most part people have concluded that ξ 0 is approximately 2 or 3 lattice constants in typical optimally doped materials. This has lead many people to conclude that these materials are nearly in a "real space pairing" limit [103][104][105][106][107], in which pairs of holes form actual two particle bound states, and then Bose condense at T c .…”
Section: Pairing Is Collective!mentioning
confidence: 99%